2020
DOI: 10.1208/s12249-020-01761-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Liquid and Semisolid Vehicles Selected for Oral Administration of Pellets and Minitablets with Diazepam: In Vitro Investigation

Abstract: The acceptability and palatability of a dosage form are extremely important to improve patient compliance. Mixing oral solid dosage forms with food carriers is often necessary to ease swallowing and provide the taste-masking effect. The present research investigated how a liquid or semisolid carrier influences the disintegration time and drug dissolution rate of pellets and minitablets with diazepam. The disintegration of pellets and minitablets in liquid carriers (water, milk and apple juice) was determined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This way of taking medicines facilitates swallowing and helps to mask their unpleasant taste, leading to better patient compliance. Furthermore, studies have shown that sprinkle formulations are more acceptable to children than liquid forms such as traditionally used syrups [ 4 , 5 ]. In recent years, numerous types of sprinkled drug products have begun to emerge and are now available in the form of immediate-release (IR), delayed-release (DR), extended-release (XR), or multiparticulate drug delivery systems (MDDS), including multiple-unit pellet systems (MUPS) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This way of taking medicines facilitates swallowing and helps to mask their unpleasant taste, leading to better patient compliance. Furthermore, studies have shown that sprinkle formulations are more acceptable to children than liquid forms such as traditionally used syrups [ 4 , 5 ]. In recent years, numerous types of sprinkled drug products have begun to emerge and are now available in the form of immediate-release (IR), delayed-release (DR), extended-release (XR), or multiparticulate drug delivery systems (MDDS), including multiple-unit pellet systems (MUPS) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that sprinkle formulations are solid dosage forms and have enhanced stability during storage compared to liquids. In addition, they make it possible to give the drug product the required release characteristics (immediate or modified) [ 4 , 6 ]. With this respect, sprinkle formulations in the form of multiparticulate pellet system (multiple-unit pellet system, MUPS) appear to be the most beneficial, as all the critical quality characteristics can be easily achieved by applying the appropriate coating layers [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%